2022
DOI: 10.1629/uksg.580
|View full text |Cite
|
Sign up to set email alerts
|

Big in Japan, Zimbabwe or Brazil – global reach and national preferences for open access books

Abstract: The perceived effect of internationalization on publishing is that there is a strong focus on global issues written in English only. In academic book publishing -strongly connected to the humanities and social sciences (HSS) -languages other than English play an important role. Non-English academic publications have been linked to regional issues: there is a tension between English as the 'lingua franca' enabling a global reach versus local languages that provide a better cultural 'fit'. This article examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…We have seen that language has a large influence on the average number of downloads, especially when we compare English to other languages. Previous research on the international usage of the OAPEN Library has shown that readers from many countries have a strong preference for books written in their native or widely used languages (Snijder 2022). For instance, the ten most downloaded books in Chile were written in Spanish, while ten French language titles are most widely read in Cote d'Ivoire.…”
Section: Discussionmentioning
confidence: 99%
“…We have seen that language has a large influence on the average number of downloads, especially when we compare English to other languages. Previous research on the international usage of the OAPEN Library has shown that readers from many countries have a strong preference for books written in their native or widely used languages (Snijder 2022). For instance, the ten most downloaded books in Chile were written in Spanish, while ten French language titles are most widely read in Cote d'Ivoire.…”
Section: Discussionmentioning
confidence: 99%
“…The tension between English and local languages is another aspect of the discussion. English as the lingua franca is, on one side, regarded as beneficial for enabling global reach and local languages that provide a better cultural fit (Snijder, 2022). On the other hand, a study by Flowerdew and Li investigated the publication choices of Chinese HSS scholars and found a link between Spanish language publications and regional subjects, and English language articles and more global issues (Snijder, 2022).…”
Section: Dominance Is Placing the English Language As Lingua Franca F...mentioning
confidence: 99%